ENT 530 Business Plan / Nadia Hanafi, Siti Nur Lukluah Samsudin, Nurhayati Mohd Sharif ... [et al.] - Hanafi, Nadia; Samsudin, Siti Nur Lukluah; Mohd Sharif, Nurhayati; Mohd Sarijil, Mohd Zulki
The MASQUERADE ENTERPRISE produce a product that easy and portable for customer to use which is functional pen with usb drive namely "Symmetry" . We will also offer specialty for our product including the slide pointer and rechargeable. The main objective is to become the founder of first multipurpose pen with the usb drive in Malaysia and usable for consumer. It appears that is no pen's product comes with variety of function here. Our business is located at the heart of Shah Alam which is Seksyen 7. It is because the area is strategic as it allows for easy access to potential customer of local, domestic and also international. Our business targeted to students and staffs of public and privates offices.